Operation Management Performance of Korean 199 Unlimited Samgyup Restaurant in Regalado Highway, Quezon City: Vol.4, No.1 (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
Korean Unlimited BBQ restaurant Samgyupsalamat is owned by YHK F&B Incorporation. Therestaurant now has 7 locations; 5 are undergoing restoration and will likely open this year, andmore than ten more are planned for Metro Manila in 2018. Samgyupsalamat owner YoungHun Ko donated to DLSU's scholarship fund.The study reveals that the majority of respondents are female between the ages of 20 and 25years old, above working student employees at the Korean 199 unlimited samgyuprestaurants, with a shift schedule of 9:00 in the morning. The respondents assess theoperation management performance in terms of store hours, scheduling, preparation,standardization, reliability, assurance, and empathy. The problems encountered by Korean199 Unlimited Restaurants in operation management are labor shortages, insufficient training,schedule inflexibility, lack of motivation, lack of communication, little recognition, no potentialgrowth, staff conflict, trust issues, and a lousy manager.The researchers conclude that the employees should have enough skills and knowledge to beeffective operation managers based on their performance. The researchers conclude that thetwo groups of respondents have the same perception of their operation managementperformance when it comes to the above-mentioned variables. The researchers thenconcluded that the employees did not mind the attitude of the manager. The researchersrecommend that the manager or owner improve their operation management, especially withtheir employee feedback, appreciate their employee's good work, and make sure that theappraisal process is a regular, fair, and constructive two-way conversation between youremployees. The researchers recommend that the manager and employee follow theguidelines of operation management. An operation team's mandate is to manage andoptimize the processes that keep a business running and generating value. The researchersrecommend that the employees follow the guidelines of operation management to improvetheir performance.
Keywords: Business